2006
DOI: 10.5713/ajas.2006.406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Enterococcus faecium SF68 on Growth Performance, Nutrient Digestibility, Blood Characteristics and Faecal Noxious Gas Content in Finishing Pigs

Abstract: The objective of this study was to investigate the effects of feeding probiotic (Enterococcus faecium SF68, EF) on growth performance, nutrient digestibility, blood characteristics and faecal noxious gas content in finishing pigs. A total of eighty [(Landrace×Yorkshire)×Duroc] pigs with an initial BW of 50.47±2.13 kg were used in this 8-week experiment. Pigs were allotted to four treatments (4 replicates per treatment and 5 pigs per pen) according to a randomized complete block design. Dietary treatments were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Our study is in agreement with the report of Yan and Kim (2013) where no differences were observed in blood characteristics. These results are also consistent with our own earlier study Chen et al (2006), in which no differences were observed after probiotic supplementation in pigs.…”
Section: Blood Profilessupporting
confidence: 83%
See 2 more Smart Citations
“…Our study is in agreement with the report of Yan and Kim (2013) where no differences were observed in blood characteristics. These results are also consistent with our own earlier study Chen et al (2006), in which no differences were observed after probiotic supplementation in pigs.…”
Section: Blood Profilessupporting
confidence: 83%
“…In recent times, the application of probiotics, in particular, has received significant attention in the pig industry (Chen et al 2006;Meng et al 2010;Yan et al 2010;Yan et al 2011). Probiotics are live microbial additives which affect the gut flora in a way that is beneficial to the host animal by improving the intestinal microbial balance (Fuller 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2006) also found that dietary E. faecium SF68 (0, 0.175, and 0.350 × 10 9 cfu/kg diet) linearly increased the apparent total tract digestibility of dry matter and nitrogen in finishing pigs. In the current study, the CAID of Cys-Gly and most essential AA were increased by 5.2-7.2% in E. faecium groups.…”
Section: Discussionmentioning
confidence: 85%
“…Un beneficio adicional de la adición de probióticos a las dietas para cerdos es la disminución del nitrógeno amoniacal en heces (Chen et al, 2006), lo que refuerza el uso de dietas con baja proteína, ya que la combinación de ambas alternativas permite disminuir la excreción de nitrógeno de manera aditiva.…”
Section: Análisis Microbiológicounclassified